Exploring synergies between human rights and public health ethics: A whole greater than the sum of its parts - Nixon Stephanie; Forman Lisa (BMC, 2008)
Abstract Background The fields of human rights and public health ethics are each concerned with promoting health and elucidating norms for action. To date, however, little has been written about the contribution that these two justificatory frameworks can make together. This article explores how a combined approach may make a more comprehensive contribution to resolving normative health issues and to advancing a normative framework for global health action than either approach made alone. We explore this synergy by first providing overviews of public health ethics and of international human rights law relevant to health and, second, by articulating complementarities between human rights and public health ethics. Discussion We argue that public health ethics can contribute to human rights by: (a) reinforcing the normative claims of international human rights law, (b) strengthening advocacy for human rights, and (c) bridging the divide between public health practitioners and human rights advocates in certain contemporary health domains. We then discuss how human rights can contribute to public health ethics by contributing to discourses on the determinants of health through: (a) definitions of the right to health and the notion of the indivisibility of rights, (b) emphasis on the duties of states to progressively realize the health of citizens, and (c) recognition of the protection of human rights as itself a determinant of health. We also discuss the role that human rights can play for the emergent field of public health ethics by refocusing attention on the health and illness on marginalized individuals and populations. Summary Actors within the fields of public health, ethics and human rights can gain analytic tools by embracing the untapped potential for collaboration inherent in such a combined approach.